TOI-836: A super-Earth and mini-Neptune transiting a nearby K-dwarf. Issue 3 (9th February 2023) - Hawthorn, Faith; Bayliss, Daniel; Wilson, Thomas G; Bonfanti, Andrea; Adibekyan, Vardan; Alibert, Yann; Sousa, Sérgio G; Collins, Karen A; Bryant, Edward M; Osborn, Ares; Armstrong, David J; Abe, Lyu; et al.
ABSTRACT: We present the discovery of two exoplanets transiting TOI-836 (TIC 440887364) using data from TESS Sector 11 and Sector 38. TOI-836 is a bright ( T = 8.5 mag), high proper motion (∼200 mas yr −1 ), low metallicity ([Fe/H]≈−0.28) K-dwarf with a mass of 0.68 ± 0.05 M⊙ and a radius of 0.67 ± 0.01 R⊙ . We obtain photometric follow-up observations with a variety of facilities, and we use these data sets to determine that the inner planet, TOI-836 b, is a 1.70 ± 0.07 R⊕ super-Earth in a 3.82-d orbit, placing it directly within the so-called 'radius valley'. The outer planet, TOI-836 c, is a 2.59 ± 0.09 R⊕ mini-Neptune in an 8.60-d orbit. Radial velocity measurements reveal that TOI-836 b has a mass of 4.5 ± 0.9 M⊕, while TOI-836 c has a mass of 9.6 ± 2.6 M⊕ . Photometric observations show Transit Timing Variations (TTVs) on the order of 20 min for TOI-836 c, although there are no detectable TTVs for TOI-836 b. The TTVs of planet TOI-836 c may be caused by an undetected exterior planet.